Functions of regulators of G protein signaling 16 in immunity, inflammation, and other diseases - Tian, Miaomiao; Ma, Yan; Li, Tao; Wu, Nijin; Li, Jiaqi; Jia, Huimin; Yan, Meizhu; Wang, Wenwen; Bian, Hongjun; Tan, Xu; Qi, Jianni (Frontiers in Molecular Biosciences, 2022)
Regulators of G protein signaling (RGS) act as guanosine triphosphatase activating proteins to accelerate guanosine triphosphate hydrolysis of the G protein α subunit, leading to the termination of the G protein-coupled receptor (GPCR) downstream signaling pathway. RGS16, which is expressed in a number of cells and tissues, belongs to one of the small B/R4 subfamilies of RGS proteins and consists of a conserved RGS structural domain with short, disordered amino- and carboxy-terminal extensions and an α-helix that classically binds and de-activates heterotrimeric G proteins. However, with the deepening of research, it has been revealed that RGS16 protein not only regulates the classical GPCR pathway, but also affects immune, inflammatory, tumor and metabolic processes through other signaling pathways including the mitogen-activated protein kinase, phosphoinositide 3-kinase/protein kinase B, Ras homolog family member A and stromal cell-derived factor 1/C-X-C motif chemokine receptor 4 pathways. Additionally, the RGS16 protein may be involved in the Hepatitis B Virus -induced inflammatory response. Therefore, given the continuous expansion of knowledge regarding its role and mechanism, the structure, characteristics, regulatory mechanisms and known functions of the small RGS proteinRGS16 are reviewed in this paper to prepare for diagnosis, treatment, and prognostic evaluation of different diseases such as inflammation, tumor, and metabolic disorders and to better study its function in other diseases.